My dad and me - Capucilli, Alyssa Satin 1957-; Mitchell, Susan 1962-. (New York, N.Y. Little Simon, 2009)
"Follow multicultural dads and children on a playful adventure through each season, and learn to say "dad" in four different languages"--P. 4 cover.
Pages are folded.
Keywords: Father and child -- Fiction; Languages, Modern -- Fiction; Seasons -- Fiction